The Heritage of War and the Discourse of Sustainability - Figenschau, Ingar (Norwegian Archaeological Review, 2019)
Since the concept of sustainability (or sustainable development) became famous through its adoption in the UN’s report, ‘Our Common Future’ in 1987, it has travelled widely to become a global and omnipresent key concept also in the field of heritage. The inclusion into this field was facilitated by the understanding of heritage as resource, which has become the norm within cultural heritage management discourses and strategies. This understanding is increasingly sustained by an associated vocabulary of concepts that promote cultural heritage sites as economically and socio-politically beneficial, emphasising their value as resources for us. This paper explores what happens when this conceptual repertoire of resource thinking is applied to WWII Wehrmacht sites in northern Norway, a heritage that previously has been othered and excluded. How does it impact on the understanding of this particular heritage and how may it be challenged and transformed through encounters with an unruly heritage that potentially defies and distances such conceptualisation?